Co(OH)2 Nanosheets Supported on Laser Ablated Cu Foam: An Efficient Oxygen Evolution Reaction Electrocatalyst - Zhou, Xinfeng; Qi, Weihong; Yin, Kai; Zhang, Ning; Gong, Shen; Li, Zhou; Li, Yejun (Frontiers in Chemistry, 2020)
Highly efficient and low-cost non-noble metal based electrocatalysts for oxygen evolution reaction (OER) have attracted more and more attention in recent years. However, the current research has been focused on the construction of novel OER electrocatalysts themselves, little attention has been paid to the modification of the substrates. In this work, a different strategy is proposed via laser ablation to fabricate the Cu foams with rich micro/nano-structures as OER substrates. Later, the precipitation conversion method was utilized to grow cobalt hydroxide on the laser fabricated Cu foams. The as-produced Cu/Cu oxides/Co(OH)2 electrocatalysts exhibit high OER activity in 1 M KOH, requiring an overpotential of only 259 mV at a current density of 50 mA cm-2 with excellent mild-term durability. The improved catalytic performance of the prepared samples can be attributed to the increased surface area, rich active sites, and the superhydrophilicity of the laser produced micro/nano-structures.